Factors shaping community assemblages and species co‐occurrence of different trophic levels. Issue 13 (23rd May 2017) - Trivellone, Valeria; Bougeard, Stephanie; Giavi, Simone; Krebs, Patrik; Balseiro, Diego; Dray, Stephane; Moretti, Marco
Abstract: Species assemblages are the results of various processes, including dispersion and habitat filtering. Disentangling the effects of these different processes is challenging for statistical analysis, especially when biotic interactions should be considered. In this study, we used plants (producers) and leafhoppers (phytophagous) as model organisms, and we investigated the relative importance of abiotic versus biotic factors that shape community assemblages, and we infer on their biotic interactions by applying three‐step statistical analysis. We applied a novel statistical analysis, that is, multiblock Redundancy Analysis (mbRA, step 1) and showed that 51.8% and 54.1% of the overall variation in plant and leafhopper assemblages are, respectively, explained by the two multiblock models. The most important blocks of variables to explain the variations in plant and leafhopper assemblages were local topography and biotic factors. Variation partitioning analysis (step 2) showed that pure abiotic filtering and pure biotic processes were relatively less important than their combinations, suggesting that biotic relationships are strongly structured by abiotic conditions. Pairwise co‐occurrence analysis (step 3) on generalist leafhoppers and the most common plants identified 40 segregated species pairs (mainly between plant species) and 16 aggregated pairs (mainly between leafhopper species). Pairwise analysis on specialist leafhoppers and potential host plants clearly revealed aggregated patterns. Plant segregation suggests heterogeneous resource availability and competitive interactions, while leafhopper aggregation suggests host feeding differentiation at the local level, different feeding microhabitats on host plants, and similar environmental requirements of the species. Using the novel mbRA, we disentangle for the first time the relative importance of more than five distinct groups of variables shaping local species communities. We highlighted the important role of abiotic processes mediated by bottom‐up effects of plants on leafhopper communities. Our results revealed that in‐field structure diversification and trophic interactions are the main factors causing the co‐occurrence patterns observed. Abstract : In this study, we investigated the relative importance of abiotic versus biotic factors that shape community assemblages by applying three‐step statistical framework. We chose two model taxa, that is, plants (producers) and leafhoppers (phytophagous), sampled in vineyard agroecosystem in southern Switzerland. In our study, we highlighted the role of abiotic filtering processes mediated by a bottom‐up effect of plants on leafhopper communities in vineyards in southern Switzerland.